Translating foreignness. Experience from a translation project carried out by a students’ project group - SMYKAŁA, MARTA (Glottodidactica, 2017)
The article partially sums up the results of a translating project realized by a students’ science club. The aim of the project was to translate into German an interview with the caretaker of the synagogue in Łańcut. The interview deals with the history of the building and the history of the former Jewish community in Łańcut. Particularly problematic in the translation process were terms originating from Yiddish or Hebrew: realia, cultural artefacts, religious terms and some other exoticisms. Another barrier was connected with the ability to approach the text from the receiver’s perspective. The article discusses those and other difficulties involved in the process of translation and some possible ways of solving them.